LARA

Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
Next revision Both sides next revision
sav08:assert_and_error_conditions [2009/03/12 16:17]
vkuncak
sav08:assert_and_error_conditions [2010/03/08 13:48]
vkuncak
Line 48: Line 48:
  
 Note: we wrote $OK \land ...$ in the weakest precondition of assume, but usually $OK$ is implicit and we do not write it.  We do not need it in other cases because it follows that right hand side implies $OK$. Note: we wrote $OK \land ...$ in the weakest precondition of assume, but usually $OK$ is implicit and we do not write it.  We do not need it in other cases because it follows that right hand side implies $OK$.
 +
  
  
Line 54: Line 55:
 Let OK denote s(error)=0 and OK' denote s'​(error)=0. ​ We define: Let OK denote s(error)=0 and OK' denote s'​(error)=0. ​ We define:
 \begin{eqnarray*} \begin{eqnarray*}
-  R_c(\mbox{havoc(x)}) &=& \{(s,​s'​) \mid OK \rightarrow (OK' \land s'​(y)=s(y)) \} \\+  R_c(\mbox{havoc(x)}) &=& \{(s,​s'​) \mid OK \rightarrow (OK' \land \bigwedge_{{y \not\equiv x} s'​(y)=s(y)) \} \\
   R_c(\mbox{assert}\ F}) &=& \{(s,​s'​) \mid (OK \land F(s)) \rightarrow s=s' \} \\   R_c(\mbox{assert}\ F}) &=& \{(s,​s'​) \mid (OK \land F(s)) \rightarrow s=s' \} \\
   R_c(\mbox{assume}\ F}) &=& \{(s,​s'​) \mid OK\ \rightarrow\ (F(s) \land s=s') \} \\   R_c(\mbox{assume}\ F}) &=& \{(s,​s'​) \mid OK\ \rightarrow\ (F(s) \land s=s') \} \\